Cytokine profiling for Egyptian diabetic patients with nephropathy - Samir, Samar; B. Abdel Gaffar, Abdel; Emara, Ibrahim; Mohamed, Rania (Journal of medicine in scientific research : JMSR : official publication of General Organization of Teaching Hospitals and Institutes, 2022)
Background Evidence suggests that poor glycemic control is significantly associated with the development of microvascular complications of diabetes such as nephropathy. Studies have indicated that interleukin 17 (IL-17), interferon gamma-inducible protein 10 (IP-10), and IL-10 are important risk factors for nephropathy. This study aimed to evaluate the cytokine profile for diabetic patients with nephropathy. Patients and methods The study included 72 diabetic patients who were divided into two groups. Group 1 included diabetic patients without complications with an albumin creatinine ratio of less than or equal to 30, while group 2 included 36 diabetic patients with an albumin creatinine ratio more than 30 and 28 subjects as a control group. Two diabetic groups were divided into two subgroups according to C-peptide levels into type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). Serum samples were collected and tested for C-reactive protein, IL-17, IL-10, and IP-10 by ELISA. Results The IL-17 and IP-10 levels were significantly increased in type 2 diabetic nephropathy patients compared with controls, but IL-10 levels were significantly increased in diabetic patients with T2DM compared with controls and T1DM. There was a significant increase for nephropathy T1DM patients than non-nephropathy patients. Conclusion Monitoring of cytokines help evaluate the immune status inflammation of diabetic nephropathy patients.